Some Physiological Parameters, Biomass Distribution and Carbon Allocation in Roots of Forage Grasses Growing under Different Nitrogen Dosages - Grayna Mastalerczuk (Science Faculty of Chiang Mai University, 2019)
The accumulation and distribution of photosynthetically fixed carbon (C) in different types of crops, and especially in roots, is important for determining the input of carbon in ecosystems. The effect of various types of nitrogen (N) fertilization on physiological parameters, biomass allocation between shoots and roots, and carbon accumulation in roots of festulolium and meadow fescue plants was evaluated. The physiological parameters (SPAD index, CO2 assimilation, transpiration rate, water-use efficiency), yield, mass of roots, harvest index, carbon content and accumulation in roots of grasses were determined. The increase in N dosage improved the SPAD index, CO2 net assimilation rate, and the harvest index of plants. However, the highest dosage of N reduced the root mass, and also carbon content, and its accumulation in the roots of plant. Regardless of N fertilization, the mean content of C in roots was low when compared with the literature (0.29 g/g). Moreover, plant photosynthetic activity was positively related to the aboveground part of plants. In contrast, it was negatively related to the belowground part. A higher allocation of biomass to the roots was associated with an increase in the C accumulation in grass roots and the reduction of plant CO2 assimilation and yield.